THE LIMITATIONS OF TECHNICAL ASSISTANCE AS A SOLUTION TO GLYPHOSATE-TOLERANT WEEDS IN NORTHERN PARAN STATE, BRAZIL (CIPEEX, 2022)
DOMINANT APPROACHES TO PREVENTING HERBICIDE-TOLERANT WEED FOCUS ON INDIVIDUAL OUTREACH AND TECHNICAL ASSISTANCE TO ENCOURAGE FARMERS TO ADOPT BEST MANAGEMENT PRACTICES. THE CASE STUDY OF SOYBEAN PRODUCERS IN NORTHERN PARAN STATE, BRAZIL, SUGGESTS THAT THIS APPROACH HAS NOT BEEN ADEQUATE, AS MANY PRODUCERS FAIL TO IMPLEMENT PREVENTATIVE PRACTICES DESPITE HAVING ACCESS TO INFORMATION AND TECHNICAL ASSISTANCE. WE IDENTIFY KEY ASSUMPTIONS OF THE TECHNICAL ASSISTANCE APPROACH TO RESISTANCE PREVENTION AND EVALUATE THEIR VALIDITY WITHIN THIS CASE STUDY, FOCUSING ON FARMER INTERACTIONS WITH HERBICIDE VENDORS AND TECHNICAL ASSISTANTS FROM AGRICULTURAL COOPERATIVES. WE CONDUCTED QUESTIONNAIRES WITH 54 SOYBEAN PRODUCERS IN NORTHERN PARAN TO GAIN AN UNDERSTANDING OF THEIR PRINCIPAL SOURCES OF TECHNICAL ASSISTANCE, THE TYPE OF TECHNICAL ADVICE THEY RECEIVE, HOW THEY DECIDE WHETHER TO IMPLEMENT THIS ADVICE, AND THE PRACTICES THAT THEY END UP IMPLEMENTING. DUE TO LIMITATIONS IN THE SAMPLING SIZE AND AVAILABLE RECRUITMENT TECHNIQUES, WE DO NOT PRESENT OUR RESULTS AS QUANTITATIVE, STATISTICALLY SIGNIFICANT CONCLUSIONS. RATHER, THIS SURVEY REPRESENTS A PRELIMINARY OVERVIEW OF TECHNICAL ASSISTANCE IN NORTHERN PARAN, OPENING THE DOOR FOR FUTURE RESEARCH. WE FOUND THAT COOPERATIVE TECHNICAL ASSISTANTS DO NOT ALWAYS RECOMMEND NON-CHEMICAL, INTEGRATED PEST CONTROL PRACTICES, AND THAT PRODUCERS FACE EXTERNAL BARRIERS TO IMPLEMENTING PREVENTATIVE PRACTICES INCLUDING THE CLOSE PROXIMITY OF HERBICIDE VENDORS.
Keywords: Glyphosate-resistant weeds; Technical assistance; Agricultural cooperatives